2015
DOI: 10.3389/fncel.2015.00485
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products and its Inflammatory Ligands are Upregulated in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disorder of largely unknown pathogenesis. Recent studies suggest that enhanced oxidative stress and neuroinflammation contribute to the progression of the disease. Mounting evidence implicates the receptor for advanced glycation end-products (RAGE) as a significant contributor to the pathogenesis of certain neurodegenerative diseases and chronic conditions. It is hypothesized that detrimental actions of RAGE are triggered upon binding to its ligands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 63 publications
(71 reference statements)
2
53
0
Order By: Relevance
“…Conversely, serum sRAGE was decreased in human ALS patients, thereby putatively increasing ligand burden available for binding to and inducing signaling through full-length RAGE [98]. While little mechanistic evidence is available linking RAGE and ALS, our laboratory recently showed that RAGE and its ligands are increased in the spinal cord of ALS patients [95].…”
Section: Amyotrophic Lateral Sclerosis Another Inflammatory Syndromementioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, serum sRAGE was decreased in human ALS patients, thereby putatively increasing ligand burden available for binding to and inducing signaling through full-length RAGE [98]. While little mechanistic evidence is available linking RAGE and ALS, our laboratory recently showed that RAGE and its ligands are increased in the spinal cord of ALS patients [95].…”
Section: Amyotrophic Lateral Sclerosis Another Inflammatory Syndromementioning
confidence: 95%
“…There is prominent overlap of disease phenotypes in ALS to other disorders with regard to the cellular consequences of RAGE-DIAPH1 signaling, although further investigation is required to elucidate these mechanisms [93]. Several studies have reported increased concentrations of RAGE ligands in the spinal cord [94][95][96] and CSF of ALS patients [97]. Conversely, serum sRAGE was decreased in human ALS patients, thereby putatively increasing ligand burden available for binding to and inducing signaling through full-length RAGE [98].…”
Section: Amyotrophic Lateral Sclerosis Another Inflammatory Syndromementioning
confidence: 99%
“…The exception to this is in lung tissue, in which RAGE is more highly expressed in the basal state in the alveolar type 1 epithelial cell [1]. In most other tissues, the expression of RAGE is low in the absence of stress and is upregulated in disease settings such as obesity [2], diabetes, neurodegeneration such as Alzheimer’s disease and amyotrophic lateral sclerosis (ALS) [3], malignant disorders [4] and autoimmune/inflammatory conditions [5], as examples. Of note, the production and accumulation of RAGE ligands also increases in these disease milieus, thereby implicating the ligand-RAGE axis in the pathogenesis of these disorders and their complications.…”
Section: 0 Introductionmentioning
confidence: 99%
“…For example, a promissory finding applicable in neurodegenerative contexts involves the hypotheses in which cell survival, specifically neuronal type, is closely connected to the ECS, given that neuronal insult triggers repair mechanisms and endogenous production of CBs, such as AEA. 88 In fact, specific detrimental proteins present in neurodegenerative diseases (ie, Ab) evoke localized and eventually general neuronal degeneration, which is also manifested in function impairment; then again, this deleterious conditions are reported to induce the production of endocannabinoids such as 2-AG, so that its neuroprotective qualities can be exerted. 89 Moreover, the ECS experiences downregulation of CBs as part of the hallmarks of some neurological diseases on early stages (usually previous to diagnosis), whereas advanced phases exhibit important receptor loss in the basal ganglia; in this form, both traits are consistent with initial hypokinetic manifestations versus advanced hyperkinetic symptoms experienced by patients in diseases such as PD or HD.…”
Section: Possible Neuroprotective Mechanisms Of Cbs In the Brainmentioning
confidence: 99%
“…Moreover, the characteristic cognitive alterations due to hippocampal dent might be modulated by the ECS through anti-inflammatory and antioxidant means-and overall neuroprotective mechanisms-in this form, several experimental strategies explored the scopes and limitations of the ECS under the pathological hallmarks of AD and continue to provide valuable information in these regards. 88,89,92 Aside of the classical signs of AD, the overactivation of the N-methyl-D-aspartate receptor (NMDAr) and the consequent dysregulation of Ca 2þ influx converge in the degenerative course of the disease. Accordingly, available information strongly suggests that the activation of CB1r could trigger protective actions along with the inhibition of excessive Ca 2þ entry; such approaches propose hitherto the upregulation of the most prominent endogenous CBs as well as the reduction in the excitotoxic events resulting from the excessive Ca 2þ influx.…”
Section: Potential Therapeutic Targets Of the Ecs In Neurodegenerativmentioning
confidence: 99%